Design of Stimuli‐Responsive Peptides and Proteins. (7th December 2022) - Li, Yang; Yang, Guangze; Gerstweiler, Lukas; Thang, San H.; Zhao, Chun‐Xia
Abstract: Stimuli‐responsive peptides and proteins are an exciting class of smart biomaterials for various applications and have received significant attention over the past decades. A wide variety of stimuli such as temperature, pH, ions, enzymes, magnetic field, redox, etc., are explored. This article provides a review of five intensively studied types of stimuli‐responsive peptides and proteins, their design principles and applications, including temperature‐, pH‐, light‐, metal ion‐, and enzyme‐responsive with an emphasis on the key design concepts and switch function. Moreover, typical examples of their applications are discussed to provide a better understanding of the design concept and underlying methodology. This review will facilitate and inspire future innovation toward new peptide‐ and protein‐based materials and their diverse applications. Abstract : This review highlights five intensively studied types of stimuli‐responsive peptides and proteins, their design principles, and applications, including temperature‐, pH‐, light‐, metal ion‐, and enzyme‐responsive smart biomolecules. This article will facilitate and inspire future innovation toward the development of new peptide‐ and protein‐based materials and their diverse applications.